Gasdermin E Does Not Limit Apoptotic Cell Disassembly by Promoting Early Onset of Secondary Necrosis in Jurkat T Cells and THP-1 Monocytes - Tixeira, Rochelle; Shi, Bo; Parkes, Michael A. F.; Hodge, Amy L.; Caruso, Sarah; Hulett, Mark D.; Baxter, Amy A.; Phan, Thanh Kha; Poon, Ivan K. H. (Frontiers in Immunology, 2018)
During the progression of necroptosis and pyroptosis, the plasma membrane will become permeabilized through the activation of mixed lineage kinase domain like pseudokinase (MLKL) or gasdermin D (GSDMD), respectively. Recently, the progression of apoptotic cells into secondary necrotic cells following membrane lysis was shown to be regulated by gasdermin E (GSDME, or DFNA5), a process dependent on caspase 3-mediated cleavage of GSDME. Notably, GSDME was also proposed to negatively regulate the disassembly of apoptotic cells into smaller membrane-bound vesicles known as apoptotic bodies (ApoBDs) by promoting earlier onset of membrane permeabilisation. The presence of a process downstream of caspase 3 that would actively drive cell lysis and limit cell disassembly during apoptosis is somewhat surprising as this could favour the release of proinflammatory intracellular contents and hinder efficient clearance of apoptotic materials. In contrast to the latter studies, we present here that GSDME is not involved in regulating secondary necrosis in human T cells and monocytes, and also unlikely in epithelial cells. Furthermore, GSDME is evidently not a negative regulator of apoptotic cell disassembly in our cell models. Thus, the function of GSDME in regulating membrane permeabilization and cell disassembly during apoptosis may be more limited.